Food consumption and food security during the COVID-19 pandemic in Addis Ababa - Hirvonen, Kalle; de Brauw, Alan; Abate, Gashaw T. (International Food Policy Research Institute, 2020)
International humanitarian organizations have expressed substantial concern about the potential for increases in food insecurity resulting from the COVID-19 pandemic. In this paper, we use a unique panel survey of a representative distribution of households in Addis Ababa to study both food security and food consumption. In contrast to some other countries in the region, Ethiopia never went into a full lockdown severely restricting movement. Despite subjective income measures suggesting a large proportion of households have been exposed to job loss or reduced incomes, we find that relative to a survey conducted in August and September of 2019, food consumption and household dietary diversity are largely unchanged or slightly increased by August 2020. We find some changes in the composition of food consumption, but they are not related to shocks found in previous phone surveys conducted with the same households. The results therefore suggest the types of subjective questions about income typically being asked in COVID-19 phone surveys may not appropriately reflect the magnitude of such shocks. They also imply, at least indirectly, that in the aggregate food value chains have been resilient to the shock associated with the pandemic.